Two distinct domains contribute to the substrate acyl chain length selectivity of plant acyl-ACP thioesterase - Fuyuan Jing (Nature Portfolio, 2018)
The substrate specificity of acyl-ACP thioesterase (TE) plays a crucial role in determining the product profile of type II fatty acid synthase. Utilizing two FatB-type acyl-ACP TEs, the authors here define determinants of substrate specificity and create synthetic enzymes with distinct catalytic traits.